A Systematic Review Trend of Learning Methods for Reading the Kitab Kuning at Pesantren (2000-2022) - Muhamad Arif; Makmur Harun; Mohd Kasturi Nor bin Abd Aziz (Universitas Nahdlatul Ulama Surabaya, 2022)
This research provides a critical analysis of several methods for learning to read the yellow book (Kitab Kuning), as well as research results published in national and international databases of journals and proceedings. Regarding the study results that generate discussions on one or two methods for reading the yellow book. Starting with this, researchers are interested in conducting critical analysis with the aid of unrecorded space and the necessity for more research using a systematic literature review. As a fresh (targeted) perspective taken by academics on how Islamic educational institutions (Islamic boarding schools-non-Islamic boarding schools) established the yellow book reading method in the 21st century. In addition, researchers need precise data on the performance of the yellow book reading approach based on 21st-century study findings. This study employs qualitative methods in conjunction with a systematic literature review approach, including collecting online article data from many national and international databases. Scopus, Sciencedirect, Emerald, Crossref, and Google Scholar are other examples. The researchers employed a variety of keywords, including